Vida útil pós-colheita de mamão Formosa Tainung tratado com 1-metilciclopropeno - Santos, Elizangela Cabral dos (2008)
This work was aimed at to evaluate the effects of 1-MCP and carnauba wax on the quality and shelf life of papaya Tainung 01 (Formosa group) grown at Acaraú valley (State of Ceará, Brazil), harvested at different maturation stages, and stored under refrigeration (at the site of production: Marco, State of Ceará) and under ambient temperature (at Embrapa Agroindústria Tropical, Fortaleza, Ceará). The fruits were treated according to the destination markets. For the domestic market, the treatments were wax 18% application (control) and wax application followed by 1-MCP. For the external market, it was utilized the following applications: wax (control), 1-MCP after wax, and wax after 1-MCP. After treatment the fruits were stored in chambers at 11 ± 1ºC and 90 ± 5% RH, for six days (domestic market) and for 12 days (external market). After storage at the site of production, the fruits were transported (under refrigeration) to the facilities at Embrapa Agroindústria Tropical (about 240 km far from the site of production), where they were then stored for a further period of 14 days at 22 ± 2ºC and 60 ± 5% RH. During this period, at intervals of two days, it was evaluated the external and internal appearances, skin and pulp colors, loss of mass, external and internal firmnesses, soluble solids content, pH, titratable acidity and vitamin C content. The experiment was conducted in a completely randomized split-plot scheme with treatments assigned to the plots (for the domestic market wax and wax + 1-MCP; for the external market wax, wax + 1-MCP, and 1-MCP + wax) and time to the subplots. The application of 1-MCP extended the shelf life of the papaya Tainung 01 fruits, independently of market destination, however more efficient when applied previously to the carnauba wax.